Prenatal diagnosis of schizencephaly. Case report and literature review - Huertas Tacchino, Erasmo (2020)
Schizencephaly is a pathology of unknown etiology characterized by clefts that communicate the subarachnoidal space with the lateral ventricles. Two types have been described since the first paper published in 1941: Type I schizencephaly (closedlip), where the edges of the cleft (lips) come into contact; Type II schizencephaly (openlip) presents cleft edges (lips) that are widely open and filled by cephalo-spinal fluid. The latter has a worse prognosis and may be diagnosed antenatally. We present the case of a fetus with prenatal ultrasonographic findings of Type 2 schizencephaly.